Ensayos sobre incubación de plantas tuberosas - Claver, Francisco Kelvin (1961)
The present paper deals with the incubation phenomenon on the following tuber bearing species: potato (Solanum tuberosum L.) ; “ulluco” (Ullucus tuberosus Loz.) ; “añu” (Tropaeolum tuberosum R. et P.) ; “oca” (Oxalis tuberosa Mol.) and “Jerusalem artichoke” (Helianthus tuberosus L.).